Patterns of speculation : a study in observational econophysics - Roehner, Bertrand M., 1946- (Cambridge University Press, 2002)
Patterns of Speculation shows how it is possible to find hidden regularities behind the bewildering diversity of historical speculative episodes, thus preparing the way for a unified theory of market speculation. A useful introduction for students of econophysics, giving an insight into economics as seen from the perspective of physics.